Uma proposta de análise técnica para linhas de transmissão compactas com potência natural elevada em regiões com topografia acidentada - Pedro Henrique Soares Vilela (2019)
A technical analysis proposal is presented to investigate the electrical parameters of a High Natural Power Transmission Line (LPNE) as a function of the number and types of towers required for its implementation in regions with rugged topography. These parameters are used to calculate the characteristic impedance value which, depending on the value of the transmission system voltage, defines the value of the Surge Impedance Loading (SIL); that is the natural MW power achieved by LPNE. The study aims to obtain and analyze the value of the natural power reached according to the possibilities of spotting the LPNE to be implanted in regions with challenging topography. Where spotting of structures becomes complex due to space constraints, high land costs, high mechanical stresses and socio-environmental constraints that this type of terrain normally presents. In the theoretical case analyzed, where the series of structures has as a typical tower the "Cross-Rope" structure, to reach the level of 1670MW of natural power in the 500kV single-circuit voltage class. It was verified that changes in the horizontal distances between phases due to the use of the 5 types of structures that make up the series, have strong interference in the value of the equivalent impedance of the Transmission Line. This influence is more significant when the incidence of the typical tower is less than 80% of the structures in the spotting, for this condition the SIL value reached by the LPNE is below the power level of 1600MW. Therefore, values below this percentage of typical tower incidence should be reviewed, that is the self-supporting light suspension towers present in the cost-optimized spotting should be replaced by heavy self-supporting towers that have cable-laying geometry equivalent to "Cross-Rope" until the required SIL value is obtained The economic analysis has shown that these changes and definitions of the structures in the spotting have a direct influence on at least 35% of the overall cost of implementing a new overhead power transmission line. Due to the impacts on cost and operational performance, the applied methodology and results obtained in this work, provides the optimization of the use of the structures, to foment new large transmission projects with high transmission capacity. In order for the National Interconnected System to have the expected operational performance with maximum efficiency in order to find the economic (measured by cost) and technical (as measured by performance) break-even point.